Influence of modified processing on structure and properties of hot isostatically pressed superalloy Inconel 718 - Rao G.A.; Srinivas M.; Sarma D.S. (My University, 2025)
Inert gas atomized (IGA) superalloy Inconel 718 powder was consolidated by hot isostatic pressing (HIPing) at 1200 °C under 120 MPa pressure for 3 h. The HIPed alloy heat treated as per the aerospace materials specification (AMS) 5662J standard schedule, viz. solution treatment (ST) at 980 °C for 1 h/water quenching (WQ) to room temperature (RT) and a two-step ageing treatment (AT) at 720 °C for 8 h/furnace cooling (FC) at 55 °C h-1 to 620 °C and holding at 620 °C for 8 h and air cooling (AC) to room temperature has exhibited the yield strength (YS) and ultimate tensile strength (UTS) comparable to that of the conventionally processed (forged and heat treated) IN 718. However, its ductility and stress rupture properties at 650 °C were found to be poor due to the presence of prior particle boundary (PPB) networks decorated with highly stable oxides (Al2O3 and TiO2) and brittle MC (Nb, Ti)C carbides. To mitigate this problem, the HIPed alloy was subjected to solution treatment at 1270 °C for 1 h followed by re-HIPing at 1100 °C/130 MPa/3 h before heat-treating it as per AMS 5662J standard schedule. Optical and scanning electron microscopy (SEM) of the alloy processed under modified HIPing and heat treatment conditions have shown the dissolution of MC-carbides, breaking up of PPB networks and formation of equiaxed grains with an average diameter of about 50 μm. Transmission electron microscopy (TEM) of this alloy has revealed uniform distribution of γ″ and γ′ strengthening precipitates in the γ-matrix and the presence of δ(Ni3Nb) phase as well as very fine oxide particles near the grain boundaries. The tensile properties of the alloy processed under modified conditions have shown quite satisfactory levels of YS and UTS combined with a significantly improved elongation (EL) values at room temperature (19.5%) and at 650 °C (8.0%). The improvement in alloy ductility was found to correlate well with the fractography of the tensile tested specimens, which showed the predominance of transgranular fracture with fine dimples at room temperature and fine dimples together with the particle boundary facets at 650 °C. The stress rupture properties of modified processed alloy at 650 °C and at a stress level of 690 MPa have shown a vastly improved rupture life of 80 h combined with 5% ductility. The improvement in tensile and stress rupture properties accomplished by the modified processing makes it possible to explore the near net shape capability of HIP technology to its full potential in the development of alloy 718 components. © 2005 Elsevier B.V. All rights reserved.